Indicators of throwing arm fatigue in elite adolescent male baseball players: A randomized crossover trial - Freeston, J.; Adams, R.; Ferdinands, R. E. D.; Rooney, K. (The Journal of Strength and Conditioning Research, 2014)
Throwing carries an inherent risk of injury that worsens in the presence of arm fatigue. The purpose of this study was to identify markers that could facilitate the early detection of this type of fatigue, by comparing the response to bouts of throwing-specific and running-based exercise. Thirteen elite junior male baseball players were tested twice, 7 days apart with a randomized crossover design. They were assessed for shoulder proprioception, maximal throwing velocity, and throwing accuracy before and after a 10-minute bout of either throwing-specific (THROW) or general (RUN) exercise. Maximal throwing velocity was reduced similarly after both THROW and RUN bouts (-1.0 ± 0.4 vs. -0.6 ± 0.2 m/s, respectively; p < 0.05); however, accuracy was only reduced after THROW (7.6 ± 3.4 cm; p < 0.05). Arm soreness increased significantly more after THROW than RUN (3.5 ± 0.7 vs. 1.4 ± 0.5 km/h, respectively; p < 0.05). Shoulder proprioception did not change after either exercise bout. The results suggest that throwing velocity is an indicator of general fatigue, whereas throwing accuracy and arm soreness are markers of arm fatigue. Shoulder proprioception does not seem to be a sensitive marker of either type of fatigue. Throwing velocity should be monitored to gauge overall fatigue levels, whereas accuracy and arm soreness should be closely monitored to gauge arm fatigue and throwing-induced injury risk.